Sociological Approach to Eradication Corruption In Indonesia (Alternative to Imprisonment) - Zaidan, Muhamad Ali (Universitas Negeri Semarang, 2017)
Hukuman penjara bagi kejahatan korupsi dalam konteks penegakan hukum kurang cukup memberikan pengaruh terhadap pelakunya. Pemberantasan korupsi sendri tidak cukup hanya dengan menggunakan pendekatan hukum, tetapi membutuhkan juga pendekatan sosial budaya, sehingga bisa dilakukan dengan lebih efektif. Sanksi pencabutan hak politik merupakan alternatif sanksi yang jauh lebih efektif dibandingkan dengan hukuman penjara. Dalam konteks ini, pendekatan sosial lebih efektif digunakan untuk memberantas korupsi.Punishment of corruption not quite put in the context of law enforcement, leading to sanctions of imprisonment. Eradication of corruption by itself no longer able to do with legal approach only, but also must use a socio-cultural approach so that corruption can be tackled effectively. Sanctioning the disenfranchisement of political rights for a time after undergoing convict prison, is a powerful tool and a non penal nature to combat corruption. Revocation of political rights to complete the imprisonment is one way to be taken by the courts to deter criminals and prevent others from doing so. The sosiological approach is one of effective method use to combat the corruption in Indonesia.